Kecurangan Akuntansi: Perspektif Penenerapan Good Corporate Governance, Ketaatan Aturan Dan Asimetri Informasi Dengan Pengendalian Internal Sebagai Variabel Intervening - Sana Sholihah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2019)
Fraud in accounting reporting is one of the factors that need to consider in presenting quality financial reports. Based on the existing phenomena, this study investigates accounting fraud that is suspected to be influenced by Good Corporate Governance (GCG), compliance with accounting rules to present financial reports and information asymmetry, and internal control. Testing the hypotheses secondary data from BUMN listed on the Jakarta Stock Exchange is used to test the allegations. Testing the hypothesis proposed using a quantitative approach with a sample of 20 BUMNs listed on the Jakarta Stock Exchange. The calculation results show that all the proposed hypotheses are empirically proven. This condition indicates that accounting fraud to be influenced by Good Corporate Governance (GCG), adherence to accounting rules for the presentation of financial statements and information asymmetry, and internal control.